THE CHANGE OF IDENTITY-PROCESS FROM THE SOCIAL SYSTEM: THE CHANGE OF IDENTITY-PROCESS FROM THE SOCIAL SYSTEM - Metodieva , Tsvetelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
According to scientific experts, in the coming years humanity will be in a process of general demographic transition, after which either the population of the planet will stabilize or an era of slight, prolonged and monotonous decline will begin. The reason for all this is the anthropogenic flow, which is gradually becoming an object of state administration, and at the same time is at the center of the scientific report.